Vitamin D Standardization Program (VDSP) intralaboratory study for the assessment of 25-hydroxyvitamin D assay variability and bias. Issue 212 (September 2021) - Wise, Stephen A.; Camara, Johanna E.; Sempos, Christopher T.; Lukas, Pierre; Le Goff, Caroline; Peeters, Stephanie; Burdette, Carolyn Q.; Nalin, Federica; Hahm, Grace; Durazo-Arvizu, Ramón A.; Kuszak, Adam J.; Merkel, Joyce; et al.
Graphical abstract: Highlights: Single-laboratory study assessed variability and bias for 12 assays for total serum 25(OH)D. All 12 assays achieved ≤ 10 % CV and 9 achieved ≤ ±5 % mean bias. Ten immunoassays exhibited changes in response for samples with high concentrations of 25(OH)D2 . Abstract: An intralaboratory study assessing assay variability and bias for determination of serum total 25-hydroxyvitamin D [25(OH)D] was conducted by the Vitamin D Standardization Program (VDSP). Thirteen assays for serum total 25(OH)D were evaluated in a single laboratory including 11 unique immunoassays and one liquid chromatography – tandem mass spectrometry (LC–MS/MS) assay. Fifty single-donor serum samples, including eight samples with high concentrations of 25(OH)D2 (> 30 nmol/L), were assigned target values for 25(OH)D2 and 25(OH)D3 using reference measurement procedures (RMP). Using four replicate measurements for each sample, the mean total percent coefficient of variation (%CV) and mean % bias from the target values were determined for each assay using the 50 single-donor samples and a 42-sample subset, which excluded 8 high 25(OH)D2 concentration samples, and compared with VDSP performance criteria of ≤ 10 % CV and ≤ ±5 % mean bias. All 12 assays achieved the performance criterion for % CV, and 9 of the 12 assays were within ≤ ±5 % mean bias. The Fujirebio Inc. assay exhibited the lowest %CV and highest percentage of individual measurements within ≤ ±5 % mean bias. Ten immunoassays exhibited changes in response due to the high 25(OH)D2 samples with Abbott, Biomérieux, DiaSorin, DIAsource, and IDS-iSYS assays having the largest deviations. The Fujirebio Inc. and Beckman Coulter assays were only minimally affected by the presence of the high 25(OH)D2 samples. Samples with high concentrations of 25(OH)D2 provided a critical performance test for immunoassays indicating that some assays may not have equal response or recovery for 25(OH)D2 and 25(OH)D3 .